SPEECH ACT IN ADVERTISING LANGUAGE OF 3 PROVIDER MOBILE PHONE PRODUCT - Suhartini Syukri; Isna Humaerah (Langkawi: Journal of The Association for Arabic and English, 2016)
This study is an analysis of selected commercial advertisement on product consumed relates to the 3 provider of mobile phone in Indonesian context. Consumers are generally believed to be active and skeptical users of information. Then, the speech act can contribute how successfulness the advertisers in persuading them. There are three kinds of act; they are locutionary act, illocutionary act and perlocutionary act. A perlocutionary act, the act that is produced as a consequences or effect of uttering a specific locution, what is brought about or achieved by saying something, in this case, the effects may be predictable by the conventional status of most illocutions, but may be force of their speech act. Using the qualitative method of research, the writers try to analyze the kinds of illocutionary forces and perlocutionary acts that occur in the advertisement through socio-pragmatic analysis. The result shows that the illocutionary acts commonly equal to the persuasive and informative as well as the advertisement goal, then the perlocutionary effects will be related to the hearers themselves.